Effects of a Storm on the Transformation and Export of Phosphorus Through a Subtropical River‐Turbid Estuary Continuum Revealed by Continuous Observation. Issue 8 (15th August 2022) - Zhang, Mingzhen; Krom, Michael D.; Lin, Jingjie; Cheng, Peng; Chen, Nengwang
Abstract: Major storms, which are increasing in frequency due to climate change, flush pollutant nutrients, including phosphorus (P), from river catchments through estuaries to the coast. Changes in P speciation alter the potential for P removal in sediments. We measured suspended particle matter (SPM), dissolved and particulate phosphorus and other physicochemical parameters at two river outlets of the Jiulong River (SE China) and a fixed station in the estuary during an entire storm (June 2019). During the storm, riverine total particulate phosphorus (TPP) more than doubled to approximately 100 μg P L −1 mainly from pollutant sources, while increased soil erosion reduced the TPP:SPM ratio by 1/3. The riverine DIP increase during the storm was only moderate (approximately 25%). As the storm intensified, the fresh‐brackish water interface moved downstream. There was increased SPM and TPP flux (up to approximately 25, 000 kg P d −1 ) from resuspended surficial sediment that had been deposited during normal flow in the adjacent tidal flats and mangrove areas. These sediments had acted as microbial incubators. Reduced Fe in the resuspended sediment was converted to labile Fe oxyhydroxides in the oxic water column, which adsorbed DIP (and probably also DOP) and increased labile TPP exported downstream. During the storm, the total flux of riverine dissolved nutrients increased while the TDN:TDP ratio decreased from 43:1 to 32:1. Our study showed that estuaries are locations for temporary deposition of labile TPP during normal flow, which are flushed out during major storms, likely resulting in increased eutrophication, including encouraging harmful algal blooms in coastal zones. Plain Language Summary: An important effect of climate change is the increase in intensity and frequency of major storms. Such storms flush pollutants including Phosphorus (P) which is often the nutrient which limits the amount of algal growth, from river catchments, through estuaries to the sea. Here, we measured dissolved and suspended P and relevant other physical and chemical data at the outlet of two branches of the Juilong river in SE China and a station in mid‐estuary during an entire storm in June 2019. We found that during the storm pollutant P (particularly that attached to particles) was flushed out of the river into the estuary. As the storm intensified, the boundary of the river‐estuary moved downstream. The increased water flow in the upper estuary resuspended pollutant‐rich sediment which had been deposited during periods of low flow. This sediment included a chemical form of Fe which removed dissolved P from the water but increased the amount of labile particulate P passing through the estuary. We conclude that major storms increase the flux of pollutant P to the coast likely causing increased eutrophication including harmful plankton blooms. Key Points: Riverine total particulate phosphorus (TPP) in stormflow was more than doubled while the increased soil erosion decreased the TPP:SPM ratio The fresh‐brackish water interface moved downstream, causing sediment resuspension, adding extra TPP flux and buffering DIP concentration Increasing labile phosphorus fluxes through the estuary with a high TDN:TDP ratio are likely contributory factors to coastal eutrophication